Delayed Leukoencephalopathy and Foreign Body Reaction After Endovascular Treatment in Patients With Intracranial Aneurysms and Aneurysmal Subarachnoid Hemorrhage—A Systematic Review of the Literature - Ridwan, Sami; Kandyba, Jörg Andreas; Schug, Anita; Malsagov, Elina; Karageorgos, Nikolaos; Hans, Franz-Josef (Frontiers in Surgery, 2021)
Background: Delayed leukoencephalopathy and foreign body reaction are rare complications after endovascular treatment of intracranial aneurysms. However, cases are increasingly being described given rising case numbers and complexity. Methods: Clinical presentation, differentials, diagnostics, treatment, and formerly published data were reviewed in light of availabe cases. A systematic search of the literature was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Results: This article provides an extensive literature review of formerly described cases and discusses causes and management of this rare, delayed complication referring to 17 articles on this topic with a total of 50 cases with sufficient data in the literature. Furthermore, we present the case of a 53-year-old female patient with subarachnoid hemorrhage from a large anterior communicating artery aneurysm with tortuous cervical vessels who was treated with endovascular coiling and suffered delayed leukoencephalopathy 6 weeks after discharge. Diagnostics, treatment, and clinical course of this rare complication are presented based on formerly published literature and this case. The patient recovered timely under high dose corticosteroid treatment and follow up MRI showed almost complete remission of the described lesions within 10 days in accordance with formerly published data. Conclusion: Foreign body reaction might result in delayed leukoencephalopathy, especially following complex endovascular aneurysm treatment. Early high dose followed by low dose ongoing corticosteroid treatment might result in timely remission.